The influence of substrates having various origins on a nutritive value of champignon mushrooms (Agaricus bisporus Imbach) - Romanjek Fajdetić, Nataša; Popović, Brigita; Parađiković, Nada; Lončarić, Zdenko, agronom; Japundžić-Palenkić, Božica (2019)
The metals such as Fe, Cu, Zn and Mn are the essential elements that have an important role in the human immune system. The aim of this research was to determine the concentration of nutritive values of macroelements (N, P, and K) and microelements (Fe and Zn) in a mushroom substrate and in a champignon mushroom fruiting body. A trial was conducted in the mushroom production company Romanjek LLC in Slavonski Brod, Croatia. It was conducted in four vegetation cycles on two different substrates, the one originating from Eastern Europe and the other originating from Northern Europe. At the end of the trial, the basic chemical properties of substrates and mushrooms were recorded. A comparison of investigated substrate measurements demonstrates that the highest content of elements N, P, and K was determined in the substrate 2 originating from Northern Europe, while the concentration of microelements Fe and Zn was higher in substrate 1, originating, from Eastern Europe. There was a statistically significant difference in a macroelement content in the mushrooms grown on the substrates of different origin, as well as in the transfer of Zn and Fe from a substrate to mushrooms. There was a higher accumulation of the transferred Zn in comparison to Fe in the mushrooms regardless of the origin of the substrate.
Šampinjoni su jedna od ekonomski najznačajnijih jestivih vrsta gljiva, iznimno dobre nutritivne vrijednosti, koja ima važnu ulogu u zdravoj prehrani. Metali Fe, Cu, Zn i Mn su esencijalni elementi koji imaju važnu ulogu u jačanju ljudskoga imuniteta. Cilj ovoga istraživanja bio je utvrditi koncentracije makroelemenata (N, P i K) i mikroelemenata (Fe i Zn) u supstratima i plodnim tijelima gljiva. Pokus je postavljen u proizvodnji gljiva Romanjek d. o. o. (Slavonski Brod, Hrvatska) i provodio se tijekom četiri vegetacijska ciklusa na dva supstrata različitoga geografskog podrijetla. Jedan supstrat (supstrat 1) proizveden je u istočnoj Europi, a drugi (supstrat 2) u sjevernoj Europi. Na kraju pokusa analizirana su osnovna kemijska svojstva supstrata i uzoraka istraživanih gljiva. Usporedbom rezultata istraživanih supstrata ustanovljen je veći sadržaj N, P i K u supstratu 2 podrijetlom sa sjevera Europe, ali je koncentracija mikroelemenata Fe i Zn bila veća u supstratu 1, podrijetlom s istoka Europe. Statistički značajna razlika ustanovljena je u sadržaju makroelemenata u gljivama uzgojenim na supstratima različitoga podrijetla, kao i u transferu Zn i Fe iz supstrata u gljive. Osim toga, uspoređujući akumulaciju transferiranoga Zn i Fe, ustanovljena je veća akumulacija Zn u gljivama bez obzira na podrijetlo supstrata.
Bibliografija: 33 jed.
Summary ; Sažetak.
Keywords: Šampinjoni -- Nutritivna vrijednost -- Teški metali -- Supstrat